Donor–Acceptor Shape Matching Drives Performance in Photovoltaics. Issue 7 (12th March 2013) - Schiros, Theanne; Kladnik, Gregor; Prezzi, Deborah; Ferretti, Andrea; Olivieri, Giorgia; Cossaro, Albano; Floreano, Luca; Verdini, Alberto; Schenck, Christine; Cox, Marshall; Gorodetsky, Alon A.; Plunkett, Kyle; et al.
Abstract While the demonstrated power conversion efficiency of organic photovoltaics (OPVs) now exceeds 10%, new design rules are required to tailor interfaces at the molecular level for optimal exciton dissociation and charge transport in higher efficiency devices. We show that molecular shape‐complementarity between donors and acceptors can drive performance in OPV devices. Using core hole clock (CHC) X‐ray spectroscopy and density functional theory (DFT), we compare the electronic coupling, assembly, and charge transfer rates at the interface between C60 acceptors and flat‐ or contorted‐hexabenzocorone (HBC) donors. The HBC donors have similar optoelectronic properties but differ in molecular contortion and shape matching to the fullerene acceptors. We show that shape‐complementarity drives self‐assembly of an intermixed morphology with a donor/acceptor (D/A) ball‐and‐socket interface, which enables faster electron transfer from HBC to C60. The supramolecular assembly and faster electron transfer rates in the shape complementary heterojunction lead to a larger active volume and enhanced exciton dissociation rate. This work provides fundamental mechanistic insights on the improved efficiency of organic photovoltaic devices that incorporate these concave/convex D/A materials.